The Effect of Supplementing Lignolitic Probiotic in Rice Straw on in Vitro Gas Production,Concentration of Ammonia (NH3),and Volatile Fatty Acid (VFA) - Prihartini, Indah; Ajeng Hariska, Viga (International Journal of Engineering and Technology, 2019)
The aims of this research were to know the effect of supplementing lignolitic probiotic in rice straw on in vitro gas production, concentration of ammonia (NH3), and VFA and to know the optimal use of lignolitic probiotic in rice straw. The materials used were rice straw and lignolitic probiotic. The methods used was Randomized Block Design (RBD) with 4 treatments and 3 groups. The treatments were P0: rice straw; P1: rice straw + 0.5% probiotic; P2 : rice straw + 1.0% probiotic; and P3: rice straw + 1.5% probiotic. The materials was incubated for 96 hours.Â  The result showed that treatments significantly affected on in vitro gas production (P
Keywords: gas production; concentration of ammonia (NH3); volatile fatty acid (VFA)